PENINGKATAN KUALITAS HIDUP PASIEN KANKER RUMAH SINGGAH MELALUI PENDAMPINGAN KELUARGA PASIEN DI YAYASAN KANKER INDONESIA (YKI) CABANG JAWA TIMUR - Fajariah, Isnaini; Fatmawati, Desy; Wahyuningtyas, Ellen; Reza, Chaerul (Program Kreativitas Mahasiswa - Pengabdian Kepada Masyarakat, 2013)
Indonesian Cancer Foundation (YKI) is a nonprofit organization that has the sole purpose of social and humanitarian field, especially in the fight against cancer that already have networks across the province in Indonesia. Halfway house is a place reserved for cancer patients who are undergoing outpatient care to facilitate the patient to reach the hospital patients who were referred for treatment. With the alternative activities that are beneficial to patients and their families, we propose a program " Improving the Quality of Life Patient Assistance Family Shelter Home through the Indonesian Cancer Foundation Patient In East Java branch ", with several objectives, namely to make cancer patients and families are always optimistic so motivated to improve their health status. Making cancer patients and families to be more productive despite the limitations physical condition. To change the behavior of the cancer patient and family so that they can always make up a healthy lifestyle. Also in this program is done by means of the method of implementation approaches, make a visit to the Indonesian Cancer Foundation to determine the condition and patient activity. Cooperation with related parties. Implementation of the program in accordance with the plans and design of program activities improved quality of life of cancer patients. Evaluation of the program and the possibility of improving the quality of the program ( program sustainability ).